Investigating the Efficiency of Coffee Husks in Bio-Retention Model for Storm Water Treatment. - Musasizi, Joseph (Kabale University, 2024)
A bio-retention is the storm water Best Management Practices (BMP) designed to capture and treat the runoff using the natural properties of soil and plants to remove contaminants. Storm water from rooftops, paved areas, bare soil and sloped lawns transports eroded soil, animal wastes, litter, salts, pesticides, fertilizers, oil and grease and other potential pollutants which flows directly into the streams and rivers. This spoils the stream water quality and thereby causing a decline in aquatic biota. However, the selection of appropriate media structure and optimized design have not been adequately researched. Additionally, the applicability of bio-retention systems has not been introduced and implemented in Uganda. Therefore, this study is aimed at investigating the efficiency of bio-retention system in the removal of storm water pollutants using coffee husks. The physical bioretention model of four Columns: J, M, N and P of 102 mm diameter and 1050mm height was developed. The layers of filter media arranged as described in table 3.2 in chapter 3. The coffee husks were introduced into columns M, N and P in varying depth leaving J as control experiment (traditional sand filter bed). Materials used in the media structure were analyzed to meet the standards according to the bioretention design manual. The quality parameters of raw stormwater composite sample were determined before passing through the model and after passing through the model at different intervals i.e., at 0, 5, 10, 20 and 30 days after introducing the coffee husks into the model. The parameters tested were Temperature, pH, Electrical Conductivity (EC), Total Dissolved Solids (TDS), Total Coliforms (TC), Faecal Coliforms (FC) or E. coli (EC), Total Suspended Solids (TSS), Biochemical Oxygen Demand (BOD), Oil & Grease (OG), Chlorides, Sulphates, Phosphorous, Turbidity and Colour. The results of the study showed that the bioretention column P drastically improved storm water quality at 30 days by reducing values of Faecal Coliforms, Total Suspended Solids, Total Coliforms, Biological Oxygen Demand and Nitrates as compared to the tested raw storm water composite sample except Colour.